The Relationship of Statins Usage and Bone Mineral Density in Postmenopausal Women - Gholamreza Dashti; Mohammadreza Salamat; Abbas Shobeiri; Amirhossein Salamat (مجله دانشکده پزشکی اصفهان, 2014)
Background: Osteoporosis is a common disease that is most prevalent in postmenopausal women. Statins are lipid lowering agents and their role in increasing bone mineral density has been reported in many studies. We conducted this study to evaluate the relationship of statin consumption and bone density in postmenopausal women.